A year in the life of an aluminous metapelite xenolith—The role of heating rates, reaction overstep, H2O retention and melt loss - Johnson, Tim; White, R.; Brown, M. (Elsevier BV, 2011)
Xenoliths of aluminous metapelite within the Platreef magmatic rocks of the Bushveld Complex, South Africa, are mineralogically and texturally zoned, with coarse-grained margins rich in acicular corundum, spinel and feldspar and cores rich in finer-grained aluminosilicate and cordierite. Xenoliths exhibiting remarkably similar features occur within other intrusions, suggesting a common origin. Using a single 3 m wide xenolith as a case study, a model is proposed to explain their petrogenesis. Mineral equilibria calculations in the NCKFMASHTO system show that the thermal stability of the solid phases, in particular corundum, is highly sensitive to the quantity of H2O retained in the protolith. Simple thermal considerations suggest the outermost 10 cm of the xenolith began to melt within a few hours following incorporation of the xenolith into the hot mafic/ultramafic magmas. Average heating rates of around 104 °C/year were sufficiently fast that the stability of low-grade hydrous phases within the protolith was overstepped by several hundred degrees, leading to retention of some or all of the structurally bound H2O to suprasolidus conditions. As a result, marginal rocks developed peritectic corundum and spinel with H2O-saturated melt, now preserved as hornfels with a (micro) diatexitic morphology. In the core of the xenolith, temperatures increased much more slowly, enabling progressive metamorphism by continual prograde reaction and loss to the margins of H2O liberated by subsolidus dehydration reactions that consumed the low-grade hydrous phases before the rocks began to melt a week or more later. Thereafter, the preservation of fine-scale bedding in xenolith cores suggests that melt was lost efficiently as it was produced. Lower H2O contents extend the upper thermal stability of aluminosilicate and cordierite to much higher temperatures, an effect exacerbated by the effects of melt loss. Whereas corundum growth occurred at the margins of the xenolith at temperatures below 800 °C, it is not predicted in the core until temperatures in excess of 1000 °C. The mineralogy and textures within the xenolith are consistent with a single-stage process involving equilibrium metamorphism and partial melting.